Numerical Bounds on the Price of Anarchy. (17th October 2017) - Grange, Louis de; Melo-Riquelme, Carlos; Burgos, Cristóbal; González, Felipe; Raveau, Sebastián
Abstract : Theoretical upper bounds for price of anarchy have been calculated in previous studies. We present an empirical analysis for the price of anarchy for congested transportation networks; different network sizes and demand levels are considered for each network. We obtain a maximum price of anarchy for the cases studied, which is notably lower than the theoretical bounds reported in the literature. This result should be carefully considered in the design and implementation of road pricing mechanisms for cities.